Evaluating the impact of e-service quality on customer intention to use video teller machine services - Nguyen Hoang Viet; Tuan Duong Vu; Bach Khoa Nguyen; Nguyen Thi My Nguyet; Do Binh; Ninh Nguyen (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Digital transformation has received increasing attention from organizations and businesses that want to remain competitive in the digital world. Many banks have increasingly been embracing electronic commerce by providing electronic banking (e-banking) services. This study aimed to investigate the impact of electronic service (e-service) quality on customer intention to use video teller machine (VTM) services. Data were obtained from 450 customers in Vietnam, where digital transformation is a priority in the development strategy of the banking industry. Structural equation modeling reveals the positive impact of three e-service quality dimensions, including responsiveness, security, and interface quality, on the perceived ease of use (PEOU), perceived usefulness (PU), and attitude toward using VTM services. The findings also demonstrate that attitudes are positively related to intention toward using VTM services, and time-consciousness strengthens this relationship. These findings extend current knowledge about e-banking services in emerging markets and provide implications for bank managers and technology providers in promoting their service quality and customer use of VTM services.
Keywords: 650; customer intention; digital transformation; e-banking services; e-service quality; video teller machine; Vietnam